Komodifikasi Penjor Di Kota Denpasar Tahun 2000 – 2015 - Mahaputra, I Wayan Gede; Wirawan, A.A. Bagus; Tagel Eddy, I Wayan (Humanis; Vol 17 No 3 (2016), 2016)
Penjor is part of Galungan ceremony. Penjor symbolized the victory of Dharma over Adharma. Penjor a means of gratitude to God. Penjor development not only as a means but also as a decoration ceremony of Bali. Penjor used as a tourist attraction, a means of competition, and as a livelihood. Penjor the local wisdom of Bali Hindu culture. Developments Penjor able to attract the younger generation to understand and maintain the cultural heritage, it is not only made to be developed but also understood its meaning so that the future can create harmony between the needs of religiosity, social, cultural, economic, and political.